A full-regenerated aggregate geopolymer ductile reinforced concrete pipe based on functionally graded design and microcapsule self-healing and a preparation method thereof

CN122345184BActive Publication Date: 2026-09-15GUANGXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610821318.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-09-15
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

[0008]本发明针对现有钢筋混凝土管作为排水管道在复杂埋地与输排水服役环境下易出现裂缝发展、渗漏通道形成及耐久性退化等问题,以及传统水泥基管道碳排放高、天然骨料消耗量大的现状,提出一种基于功能梯度设计与微胶囊自愈合的全再生骨料地聚物韧性钢筋混凝土管及其制备方法

Benefits of technology

[0031] 1. By radially configuring a dense impermeable layer and a reinforcing steel load-bearing and crack-resistant layer along the pipe wall, and by employing gradient variations in cementitious material content, aggregate particle size distribution, or fiber content, the inner wall of the pipe achieves high density and low permeability, while the outer wall achieves high load-bearing capacity and post-cracking toughness. With this gradient design, the 28-day compressive strength reaches 70 MPa, the flexural strength reaches 10.0 MPa, the seepage height is reduced to 6 mm, and the chloride ion diffusion coefficient is as low as 4.1 × 10⁻⁶. -12 m 2 /s.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122345184B_ABST
    Figure CN122345184B_ABST
Patent Text Reader

Abstract

The application discloses a kind of full recycled aggregate geopolymer ductile reinforced concrete pipe based on function gradient design and microcapsule self-healing and preparation method thereof, belong to green building material and underground pipeline engineering technical field.Concrete pipe includes at least composite inner layer and outer layer along radial direction: inner layer is full recycled fine aggregate geopolymer mortar dense impermeable layer;Outer layer is full recycled coarse aggregate and fine aggregate geopolymer concrete load crack resistance layer, and steel reinforcement cage is arranged in inner layer and outer layer;Microcapsule with mineralized bacteria liquid and nutrient in it is distributed in geopolymer mortar and concrete. Inner layer and outer layer are gradient change in cementitious material content, aggregate particle size composition or fiber content.The method includes preparation of geopolymer mortar and concrete, making steel reinforcement cage, centrifugal pipe compounding and curing.The application considers inner layer impermeability and outer layer load crack resistance, improves durability by microbial mineralization self-healing, uses industrial solid waste and construction solid waste as main raw material, and is suitable for municipal drainage and underground engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of green building materials and underground pipeline engineering technology, and in particular to a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, using industrial solid waste and construction solid waste as raw materials, and its preparation method. Background Technology

[0002] Reinforced concrete drainage pipes are among the most widely used pipe materials in municipal stormwater and sewage collection and transportation, underground pipe networks, and integrated pipe corridors. They possess characteristics such as high load-bearing capacity, strong adaptability to underground environments, and mature construction technology, playing a vital role in urban operation and public safety. With the acceleration of urbanization, increased development intensity of underground space, and the lengthening service life of pipe networks, drainage pipes face increasingly stringent requirements in terms of structural load-bearing capacity, crack control, impermeability, and long-term durability under the combined effects of external pressure loads, traffic dynamic loads, uneven settlement, groundwater level fluctuations, and complex corrosive media. However, in actual service, reinforced concrete drainage pipes may still experience problems such as crack development, leakage, increased risk of steel corrosion, and durability degradation, thereby affecting the operational safety and service life of the pipe network.

[0003] From a materials and resource perspective, traditional reinforced concrete drainage pipes are typically made using ordinary Portland cement and natural sand and gravel aggregates. Cement production is energy-intensive and generates significant carbon emissions, making it a major carbon source in the building materials sector. Simultaneously, the large-scale mining of natural aggregates places long-term pressure on the ecological environment. Therefore, achieving the substitution of low-carbon cementitious materials and the recycling of aggregate resources while ensuring the structural safety and durability of reinforced concrete drainage pipes has become an important technological direction in the field of pipeline engineering.

[0004] To reduce carbon emissions and promote resource recycling, existing technologies are gradually exploring the use of industrial solid waste (such as fly ash and slag) to prepare geopolymer cementitious systems to replace some cement, and the use of recycled construction waste aggregates to replace natural aggregates in concrete pipe production. Geopolymer materials, using solid waste as precursors, form a cementitious structure through alkali activation, possessing potential low-carbon advantages; the application of recycled aggregates helps reduce construction waste accumulation and lower natural aggregate consumption. However, recycled aggregates typically exhibit characteristics such as high water absorption, large porosity, adhesion to old mortar, and gradation fluctuations, affecting the workability of the mixture and the stability of the centrifugal molding process. The hardened interface transition zone is relatively weak, and permeability channels and micro-defects are more easily formed. Therefore, reinforced concrete drainage pipes prepared using recycled aggregate geopolymer systems still face engineering application risks in terms of crack control, impermeability, and long-term durability, making it difficult to consistently meet indicators such as impermeability grade, water absorption rate, crack width limits, and reinforcement cover durability requirements under complex service environments.

[0005] From a structural and stress mechanism perspective, reinforced concrete drainage pipes are typical components controlled by external pressure. The reinforcing steel skeleton bears tensile stress and limits crack propagation, while the concrete wall needs to simultaneously meet requirements for load-bearing capacity, impermeability, and durability. Existing pipe products mostly adopt a homogeneous structure with materials and properties largely consistent along the pipe wall thickness, making it difficult to optimize for different service priorities. On the one hand, the inner wall is in long-term contact with sewage / rainwater and dissolved salts, making it susceptible to seepage and chemical erosion, thus requiring higher density and impermeability. On the other hand, the outer wall is on the side subject to soil and load, making it more significantly affected by external pressure and settlement, and more sensitive to crack resistance and toughness. Homogeneous structures often require a trade-off between "improving density and impermeability" and "enhancing crack resistance / controlling cracking," thereby limiting the overall performance improvement of reinforced concrete drainage pipes.

[0006] Furthermore, to improve the cracking and leakage problems of reinforced concrete drainage pipes, existing technologies typically employ measures such as fiber reinforcement, internal wall coating, anti-corrosion lining, external waterproofing layer, or post-grouting repair. However, these measures are mostly passive protection or post-repair: on the one hand, they are difficult to actively inhibit the formation of leakage channels in the early stages of crack initiation; on the other hand, the construction and maintenance processes are complex and costly, and their compatibility with centrifugal molding and large-scale production is limited. In recent years, self-healing concrete materials have attracted attention. Among them, microbial induced calcium carbonate precipitation (MICP) technology utilizes microbial metabolism to induce mineralization reactions, generating calcium carbonate crystals inside cracks to achieve crack sealing, providing a new approach to improving the impermeability and durability of concrete. However, existing MIP-related research is mostly focused on ordinary concrete materials or laboratory-scale verification. In the engineering scenario of reinforced concrete drainage pipes, which are "controlled by external pressure, require crack limit management, and rely on centrifugal molding," the compatibility and synergistic mechanism between MIP and recycled aggregate geopolymer systems and steel reinforcement structures still lack a systematic solution.

[0007] In summary, existing reinforced concrete drainage pipe technology still faces prominent contradictions under the background of green, low-carbon, and resource utilization: on the one hand, it is necessary to improve the utilization level of solid waste and recycled aggregates and reduce carbon emissions; on the other hand, it is essential to meet the engineering requirements of reinforced concrete drainage pipes for structural load-bearing capacity, crack control, impermeability, and durability. Especially under the condition of a fully recycled aggregate and geopolymer cementitious system, how to achieve functional synergy of "dense and impermeable inner wall - load-bearing and crack-resistant outer wall" through reasonable pipe wall structure design, and further improve the long-term controllability of cracks and leakage through an industrially integrated self-healing mechanism, still lacks a systematic, manufacturable, verifiable, and scalable technical solution. Therefore, it is necessary to propose a novel fully recycled aggregate geopolymer tough reinforced concrete pipe and its preparation method based on functional gradient design and microcapsule self-healing for reinforced concrete drainage pipe applications, to meet the urgent needs of modern municipal and underground engineering for high-performance, long-life, green, and low-carbon drainage pipes. Summary of the Invention

[0008] This invention addresses the problems of crack development, leakage channels, and durability degradation in existing reinforced concrete pipes used as drainage pipelines under complex underground and water supply and drainage environments, as well as the high carbon emissions and large consumption of natural aggregates in traditional cement-based pipes. It proposes a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, along with its preparation method. The concrete pipe uses an industrial solid waste geopolymer cementing system instead of a cement cementing system and recycled construction waste aggregate instead of natural aggregates, achieving green, low-carbon, and resource-efficient utilization. Simultaneously, a functional gradient configuration of "internal dense impermeability—external load-bearing and crack-resistant" is introduced in the pipe wall thickness direction, and a microbial-induced calcium carbonate precipitation (MICP) microcapsule self-healing system is integrated into the pipe material to improve the long-term controllability of cracks and leakage. This achieves a synergistic unity of structural load-bearing capacity, crack control, impermeability and durability, and low-carbon manufacturing, making it suitable for municipal stormwater and sewage pipe networks, integrated pipe corridors, and underground engineering projects.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] This invention provides a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, comprising at least an inner layer and an outer layer arranged sequentially and compositely in the radial direction, which together form an integral structure.

[0011] The inner layer is a dense, impermeable layer, cast from geopolymer mortar without coarse aggregate, and reinforced with a steel skeleton. The geopolymer mortar comprises recycled fine aggregate, geopolymer cementitious material, and microcapsules; the microcapsules are uniformly distributed throughout the mortar. Enriching the mortar and optimizing the fine aggregate gradation improves the mortar's encapsulation and porosity, resulting in excellent impermeability and resistance to media erosion, thus reducing the risk of internal wall leakage. The inner layer provides impermeability and corrosion resistance.

[0012] The outer layer is a reinforced load-bearing and crack-resistant layer, cast from polymer concrete, and contains a steel reinforcement skeleton to provide structural load-bearing capacity and crack control. The polymer concrete comprises recycled coarse aggregate, recycled fine aggregate, polymer cementitious material, fibers, and microcapsules; the fibers and microcapsules are uniformly distributed throughout the polymer concrete. This outer layer provides overall load-bearing capacity and crack resistance.

[0013] The microcapsules contain bacterial solution with calcium carbonate mineralization capabilities and nutrients, enabling the concrete pipe to autonomously repair microcracks caused by external pressure loads, settlement, or environmental factors during service by inducing calcium carbonate precipitation through microorganisms. When cracks occur and water enters, the microcapsules open or break under stress or the influence of the medium, releasing the bacterial solution. Microorganisms metabolize within the crack area and induce calcium carbonate precipitation, generating calcium carbonate crystals inside the crack to fill it and restore the material's density and impermeability.

[0014] The steel reinforcement cage includes circumferential steel bars and longitudinal steel bars, which are connected to form a steel cage structure and arranged along the perimeter of the pipe.

[0015] Furthermore, the inner and outer layers exhibit a gradient change in the radial direction regarding one of the following parameters: cementitious material content, aggregate particle size distribution, or fiber content. This achieves a transition from "dense and impermeable" to "load-bearing and crack-resistant" performance from the inside out, thereby accommodating the differentiated requirements of impermeability of the inner wall and load-bearing capacity of the outer wall.

[0016] Furthermore, the geopolymer cementitious material is obtained through an alkaline activation reaction using one or more of fly ash, slag, and steel slag as precursors. When fly ash, slag, and steel slag are used as precursors, the mass ratio of fly ash, slag, and steel slag is 5:3:2. The alkaline activator used in the alkaline activation reaction is sodium hydroxide, water glass, or a composite activation system of two of these.

[0017] Furthermore, the fiber is steel fiber, polypropylene fiber, basalt fiber or any combination thereof, and the volumetric content of the fiber is 0.5%-1.5% of the volume of the geopolymer cementitious material in the geopolymer concrete.

[0018] Furthermore, the median particle size D50 of the microcapsules is 300 μm and the average wall thickness is 15 μm; the dosage of the microcapsules in the geopolymer mortar is 1%-5% of the mass of the geopolymer cementitious material in the geopolymer mortar; the dosage of the microcapsules in the geopolymer concrete is 1%-5% of the mass of the geopolymer cementitious material in the geopolymer concrete.

[0019] Furthermore, the diameter of the circumferential reinforcing bars is ≥4.0 mm, and the net spacing of the circumferential reinforcing bars is 35-120 mm; the diameter of the longitudinal reinforcing bars is ≥4.0 mm, the spacing of the longitudinal reinforcing bars is ≤400 mm, and the number of longitudinal reinforcing bars is ≥6.

[0020] When the pipe wall thickness is ≤100 mm, single-layer reinforcement is used, and the steel reinforcement cage is set at 2 / 5 of the distance from the inner wall of the pipe; when the pipe wall thickness is >100 mm, double-layer reinforcement is used, and the inner and outer concrete cover thickness of the circumferential reinforcement is not less than 20 mm, and the inner concrete cover thickness of the longitudinal reinforcement is not less than 15 mm.

[0021] Furthermore, the recycled coarse aggregate and recycled fine aggregate are both derived from construction solid waste and are obtained after crushing, screening, impurity removal and gradation adjustment.

[0022] The present invention also provides a method for preparing the fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, comprising the following steps:

[0023] Step A1, preparing geopolymer mortar: dry mix the recycled fine aggregate, geopolymer cementitious material and microcapsules evenly, then add the alkali activator solution and mixing water and continue to wet mix evenly;

[0024] Step A2, preparing geopolymer concrete: Dry mix recycled coarse aggregate, recycled fine aggregate, geopolymer cementitious material, fiber and microcapsule evenly, then add alkali activator solution and mixing water and continue to wet mix evenly;

[0025] Step A3: Fabricate the steel reinforcement cage and place it into the pipe mold, using positioning measures to ensure the steel reinforcement cage is in the designed position in the thickness direction of the pipe body;

[0026] Step A4: Using centrifugal pipe-making technology, polymer concrete and polymer mortar are compositely molded in the same pipe mold to obtain a pipe with an inner layer and an outer layer.

[0027] Step A5: After centrifugation molding, the concrete pipe is cured to obtain a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing.

[0028] Further, the alkaline activator solution is a mixture of sodium hydroxide solution and water glass, wherein the concentration of the sodium hydroxide solution is 8-12M and the modulus of the water glass is M=2.0-2.5; the liquid-to-solid ratio of the alkaline activator solution in step A1 to the geopolymer cementitious material in step A1 is 0.40-0.48; the liquid-to-solid ratio of the alkaline activator solution in step A2 to the geopolymer cementitious material in step A2 is 0.40-0.48.

[0029] Furthermore, the preparation method of the microcapsules in step S2 includes: mixing a sodium alginate aqueous solution with a mass fraction of 1.5%-2.5% with bacterial culture with calcium carbonate mineralization ability cultured to the logarithmic phase and its nutrient components, dropping the mixture into a CaCl2 cross-linking curing bath to gel into spheres, then immersing the spheres in an acidic chitosan solution with a mass fraction of 0.2-0.6% for secondary chitosan coating, followed by low-temperature drying and sealing for storage, and then immersing the coated microcapsules in a diluted silica sol / water glass solution to form a thin inorganic outer layer to enhance alkali resistance, resulting in microcapsules with a median particle size D50 of 300 μm and an average wall thickness of 15 μm.

[0030] This invention achieves multiple technological gains in reinforced concrete pipes in terms of structural load-bearing capacity, crack control, impermeability and durability, and green and low-carbon manufacturing through the synergistic design of functionally graded pipe wall configuration, microcapsule self-healing system, and fully recycled aggregate geopolymer cementitious system. The specific beneficial effects are as follows:

[0031] 1. By radially configuring a dense impermeable layer and a reinforcing steel load-bearing and crack-resistant layer along the pipe wall, and by employing gradient variations in cementitious material content, aggregate particle size distribution, or fiber content, the inner wall of the pipe achieves high density and low permeability, while the outer wall achieves high load-bearing capacity and post-cracking toughness. With this gradient design, the 28-day compressive strength reaches 70 MPa, the flexural strength reaches 10.0 MPa, the seepage height is reduced to 6 mm, and the chloride ion diffusion coefficient is as low as 4.1 × 10⁻⁶. -12 m 2 / s.

[0032] 2. Microcapsules are dispersed in polymer mortar and / or polymer concrete. When microcracks develop in the pipe during service due to external pressure, settlement, or environmental factors, the microcapsules rupture, releasing bacterial fluid and nutrients with calcium carbonate mineralization capabilities. This microbial metabolism induces calcium carbonate precipitation, achieving self-sealing of the cracks. The concrete pipe prepared according to this invention, with an initial crack width of 0.3 mm at a microcapsule dosage of 1%, reduced to 0.08 mm after 28 days of self-healing, achieving a healing rate of 73%. Increasing the microcapsule dosage to 5% further improved the healing rate to 83%, while the healing rate without microcapsules was only 8%. This self-healing mechanism effectively inhibits the formation of leakage channels and the risk of steel reinforcement corrosion, extending the service life of the pipeline.

[0033] 3. By using industrial solid wastes such as fly ash, slag, and steel slag to form a geopolymer cementing system through alkali activation, and replacing natural aggregates with 100% recycled aggregates from construction solid waste, the high energy consumption and high carbon emissions of traditional silicate cement production are avoided, while solving the problems of construction waste storage and over-mining of natural aggregates.

[0034] 4. The inner layer of polymer mortar and the outer layer of polymer concrete can be compositely formed in the same pipe mold through centrifugal pipe making process, without changing the main equipment and process flow of the existing reinforced concrete pipe production line; the reinforcement cage ensures the design position through positioning measures, and the reinforcement parameters and protective layer thickness meet the requirements of current specifications, with good engineering feasibility and quality control.

[0035] 5. Compared with homogeneous fully recycled aggregate geopolymer reinforced concrete pipes without fiber and microcapsule incorporation, this invention reduces the water penetration height from 20 mm to below 7.2 mm, decreases the chloride ion diffusion coefficient by approximately 36%, and increases the crack healing rate from 8% to over 70% while maintaining a similar aggregate content. Compared with functional gradient pipes without microcapsules incorporation, the water penetration height is further reduced from 13.5 mm to 7.2 mm, and the healing rate is increased from 27% to over 73%, fully verifying the synergistic effect of functional gradient and microcapsule self-healing. Attached Figure Description

[0036] Figure 1 This is a structural schematic diagram of the fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, according to the present invention.

[0037] Figure 2 This is a schematic diagram of the component distribution of the inner and outer layers of the present invention.

[0038] Figure 3 This is a schematic diagram of the steel reinforcement cage of the present invention.

[0039] The markings in the diagram are as follows: 1-Inner layer, 2-Outer layer, 3-Reinforcing steel skeleton, 4-Schematic diagram of inner layer section, 5-Schematic diagram of outer layer section, 6-Recycled coarse aggregate, 7-Recycled fine aggregate, 8-Microcapsule, 9-Fiber, 10-Geopolymer mortar, 11-Geopolymer concrete, 12-Circumferential reinforcement, 13-Longitudinal reinforcement. Detailed Implementation

[0040] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0041] like Figure 1-3 As shown, the present invention provides a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing, comprising an inner layer 1 and an outer layer 2 arranged sequentially and compositely in the radial direction, which together form an integral structure.

[0042] The inner layer 1 is a dense impermeable layer, which is cast from geopolymer mortar 10, and a steel reinforcement skeleton 3 is provided in the inner layer 1; the geopolymer mortar 10 includes recycled fine aggregate 7, geopolymer cementitious material and microcapsules 8; the microcapsules 8 are evenly distributed in the geopolymer mortar 10;

[0043] The outer layer 2 is a steel-reinforced load-bearing and crack-resistant layer, which is cast from geopolymer concrete 11, and a steel reinforcement skeleton 3 is provided inside the outer layer 2; the geopolymer concrete includes recycled coarse aggregate 6, recycled fine aggregate 7, geopolymer cementitious material, fiber 9 and microcapsules 8; the fiber 9 and microcapsules 8 are uniformly distributed in the geopolymer concrete 11.

[0044] The steel reinforcement cage 3 includes circumferential steel bars 12 and longitudinal steel bars 13, which are connected to form a steel cage structure and arranged along the perimeter of the pipe.

[0045] The reinforced concrete pipes prepared in the following embodiments are all centrifugally formed precast pipes, and the nominal inner diameter D is selected as an example. o The pipe has a diameter of 1000 mm, a length L of 2000 mm, and a wall thickness t of 120 mm. The pipe wall consists of an outer layer 2 and an inner layer 1, which are formed in one composite step along the radial direction. Since the wall thickness is greater than 100 mm, the reinforcing steel cage 3 adopts a double-layer reinforcing cage, including an inner reinforcing cage and an outer reinforcing cage. The two are stably concentrically positioned by positioning clips and protective layer spacers. The reinforcing steel material is hot-rolled ribbed steel bar or hot-rolled plain round steel bar. The diameter of the circumferential reinforcing bars 12 (circumferential bars) is not less than 4.0 mm, and the net spacing of the circumferential bars is controlled between 35 and 120 mm. The number of longitudinal reinforcing bars 13 (longitudinal bars) is not less than 6 and the diameter is not less than 6 mm. The spacing of the longitudinal bars is not greater than 400 mm, and 1-2 densified circumferential bars are set at the pipe ends to improve the end crack resistance and impact resistance. The protective layer thickness meets the following requirements: the thickness of the inner and outer protective layers of the circumferential bars is not less than 20 mm, and the thickness of the inner protective layer of the longitudinal bars is not less than 15 mm.

[0046] The parameters of the raw materials used in the following examples and comparative examples are as follows:

[0047] Fly ash: Grade 1, specific surface area > 400 m² 2 / kg, fineness <12%, activity index >75%.

[0048] Slag: S95 slag, specific surface area >350m² 2 / kg.

[0049] Steel slag: Specific surface area > 450 m² 2 / kg, CaO>40% (mass percentage).

[0050] Alkali activator solution: The sodium hydroxide solution used has a concentration of 8-12M and a water glass modulus of M=2.0-2.5.

[0051] Recycled aggregate: Class I recycled aggregate, water absorption <3%, crushing index <12%, apparent density >2450 kg / m³ 3 The porosity is less than 47%.

[0052] Example 1

[0053] (1) Raw material usage

[0054] ① Geopolymer mortar:

[0055] Recycled fine aggregate (0-4.75 mm); wherein the gradation composition of the recycled fine aggregate (by mass percentage) is:

[0056] 0-0.6 mm: 40%;

[0057] 0.6-1.18 mm: 30%;

[0058] 1.18-2.36 mm: 20%;

[0059] 2.36-4.75 mm: 10%.

[0060] The total amount of recycled fine aggregate is 270.00 kg;

[0061] Total geopolymer cementitious materials: 120.00 kg (60.00 kg fly ash, 36.00 kg slag, and 24.00 kg steel slag);

[0062] Total amount of alkaline activator solution: 54.00 kg (36.00 kg of water glass and 18.00 kg of NaOH solution).

[0063] Mixing water: 7.00 kg;

[0064] Microcapsules (1% of the mass of the geopolymer gelling material): 1.20 kg.

[0065] ②Geopolymer concrete:

[0066] Recycled coarse aggregate (5-20 mm): 196.00 kg;

[0067] Recycled fine aggregate (0-4.75 mm): 156.00 kg;

[0068] The gradation composition of the outer aggregate layer (by mass percentage) is as follows:

[0069] Recycled coarse aggregate (5-10 mm): 60%;

[0070] Recycled coarse aggregate 10-20 mm: 40%;

[0071] Recycled fine aggregate (0-1.18 mm): 20%;

[0072] Recycled fine aggregate (1.18-2.36 mm): 30%;

[0073] Recycled fine aggregate 2.36-4.75 mm: 50%.

[0074] Total geopolymer cementitious materials: 96.00 kg (48.00 kg fly ash, 28.80 kg slag, and 19.20 kg steel slag);

[0075] Total amount of alkaline activator solution: 46.0 kg (30.00 kg of water glass and 16.00 kg of NaOH solution).

[0076] Mixing water: 5.00 kg;

[0077] Steel fiber (volume content = steel fiber volume / geopolymer cementitious material volume = 1%): 3.35 kg;

[0078] Microcapsules (1% of the mass of the geopolymer gelling material): 0.96 kg.

[0079] ③ Reinforcing steel cage (reinforcement):

[0080] The inner layer 1 and outer layer 2 steel reinforcement cages 3 are both connected in the form of circumferential steel bars and longitudinal steel bars to form a steel cage structure. The circumferential steel bars 12 (circular bars) have a diameter of φ5 mm and a net spacing of 70 mm. The longitudinal steel bars 13 (longitudinal bars) consist of 8 evenly distributed φ8 mm longitudinal bars with a spacing of 350 mm. Two dense circumferential bars (net spacing of 45 mm) are set at each pipe end. The position of the steel reinforcement cage 3 is controlled by protective layer spacers and positioning clips to ensure that the thickness of the protective layer inside and outside the circumferential bars is 25 mm and the thickness of the protective layer inside the longitudinal bars is 25 mm, and to ensure that the steel cage has no obvious twisting deformation.

[0081] (2) Preparation method:

[0082] a) Preparation of microcapsules 8: Microcapsules 8 were prepared using a method of "sodium alginate ion gelation into spheres + composite coating enhancement": Sodium alginate was prepared into a 2% (w / w) aqueous solution, degassed, and then gently mixed with bacterial culture (such as Sporosarcina pasteurii) cultured to the logarithmic phase and possessing calcium carbonate mineralization ability, along with its nutrient components (such as urea and necessary micronutrients) to obtain a bacterial core material solution; the bacterial core material solution was loaded into a syringe or peristaltic pump and dripped into a CaCl2 crosslinking curing bath via needle dripping / extrusion for external gelation. The CaCl2 curing bath concentration was 0.15 M, and curing was carried out under low-speed stirring for 30 min to form stable calcium alginate gel microcapsules. The microcapsule particle size could be controlled by the needle specification and dripping conditions; for example, a 25G needle could form microbeads of approximately 0.5~1 mm, while a 23G needle could form microbeads of 1~2 mm. Microbeads (the particle size increases with the needle diameter) were used to obtain microcapsules within the target particle size range. After curing, the microcapsules were washed three times with deionized water and drained. If necessary, they were immersed in a 0.4% (w / w) acidic chitosan solution for a second coating for 15 min. The polyelectrolyte of alginate and chitosan was used to form a composite film to improve the structural stability and environmental resistance of the microcapsules. The coated microcapsules were briefly immersed in a diluted silica sol / water glass solution to form a thin inorganic coating to enhance alkali resistance. Finally, they were dried at a low temperature of no more than 25°C by air drying or freeze drying until surface dry or constant weight and then sealed for storage. This yielded microcapsules 8 for encapsulating bacterial culture and nutrients for self-healing systems. At this point, the median particle size D50 of microcapsules 8 was 300 μm and the average wall thickness was 15 μm.

[0083] b) Preparation of geopolymer mortar 10: First, dry mix the recycled fine aggregate, fly ash, slag, steel slag and microcapsules for 60 s, then add alkali activator solution and mixing water and continue wet mixing for 120 s, controlling the flowability of the mortar to 180-200 mm.

[0084] c) Preparation of geopolymer concrete 11: First, dry mix recycled coarse aggregate, recycled fine aggregate, fly ash, slag, steel slag, fiber and microcapsules for 60 s, then add alkali activator solution and mixing water and continue wet mixing for 120 s, controlling the flowability at the outlet to 180-200 mm.

[0085] d) Fabricate the steel reinforcement cage 3 and place it into the pipe mold;

[0086] e) Using a centrifugal pipe-making process, first add the polymer concrete 11 to cylinder A and the polymer mortar 10 to cylinder B. Then, use a pumping method to transport the polymer concrete 11 from cylinder A to the centrifugal pipe-making machine. Use a centrifugal process to cast the outer layer 2 of the pipe. After the required thickness of the outer layer 2 is reached, use the same method to simultaneously pump the polymer concrete 11 and the polymer mortar 10 into the pipe-making machine for 1 minute. Then, stop pumping the polymer concrete 11 and only keep pumping the polymer mortar 10. Continue to use a centrifugal process to cast the inner layer 1 of the pipe until the specified thickness of the inner layer 1 is reached, thus achieving one-time composite molding.

[0087] f) After centrifugal molding, the concrete pipe is steam cured at 60℃ for 8 hours, and then wet cured at room temperature for 28 days to obtain the finished concrete pipe.

[0088] (3) Performance results

[0089] 28-day compressive strength: 60 MPa;

[0090] 28-day flexural strength: 9.0 MPa;

[0091] Chloride ion diffusion coefficient: 4.6 × 10⁻⁶ -12 m 2 / s;

[0092] Seepage height: 7.2 mm;

[0093] Carbonization depth: 6 mm;

[0094] Initial crack width: 0.3 mm; crack width after 28 days of self-healing: 0.08 mm; healing rate: 73%.

[0095] Example 2

[0096] (1) Raw material usage (kg / m³) 3 )

[0097] The content of the geopolymer cementitious material in the inner layer 1 was reduced from 550 kg / m³ in Example 1. 3 Increased to 680 kg / m 3 The content of the geopolymer cementitious material in the outer layer 2 was reduced from 550 kg / m³ in Example 1. 3 Reduced to 420 kg / m 3 The remaining parameters are consistent with those in Example 1, thus creating a gradient difference of 260 kg / m 3 Specifically:

[0098] Inner layer 1: 1250 recycled fine aggregate; 680 geopolymer cementitious material (340 fly ash, 204 slag, 136 steel slag); 306 alkali activator solution; 30 mixing water; 6.8 microcapsules.

[0099] Outer layer 2: 920 recycled coarse aggregate; 820 recycled fine aggregate; 420 geopolymer cementitious material (210 fly ash, 126 slag, 84 steel slag); 202 alkali activator solution; 25 mixing water; 14.7 fiber; 4.2 microcapsules.

[0100] (2) Preparation method

[0101] Same as Example 1.

[0102] (3) Performance results

[0103] 28-day compressive strength: 70 MPa;

[0104] 28-day flexural strength: 10.0 MPa;

[0105] Chloride ion diffusion coefficient: 4.1 × 10⁻⁶ -12 m 2 / s;

[0106] Seepage height: 6 mm;

[0107] Initial crack width: 0.30 mm; crack width after 28 days of self-healing: 0.07 mm; healing rate: 77%.

[0108] Example 3

[0109] (1) Raw material usage

[0110] Except for the microcapsule dosage being changed to 5% of the mass of the geopolymer cementitious material, the other parameters are the same as in Example 1.

[0111] (2) Preparation method

[0112] Same as Example 1.

[0113] (3) Performance results

[0114] 28-day compressive strength: 60.1 MPa;

[0115] 28-day flexural strength: 8.8 MPa;

[0116] Chloride ion diffusion coefficient: 4.6 × 10⁻⁶ -12 m 2 / s;

[0117] Seepage height: 7 mm;

[0118] Carbonization depth: 5.6 mm;

[0119] Initial crack width: 0.3 mm; crack width after 28 days of self-healing: 0.05 mm; healing rate: 83%.

[0120] Example 4

[0121] (1) Raw material usage

[0122] Except that the mass fraction of sodium alginate aqueous solution was changed to 1.5%, the other parameters were the same as in Example 1.

[0123] (2) Preparation method

[0124] Same as Example 1.

[0125] (3) Performance results

[0126] 28-day compressive strength: 60 MPa;

[0127] 28-day flexural strength: 8.9 MPa;

[0128] Chloride ion diffusion coefficient: 4.4 × 10⁻⁶ -12 m 2 / s;

[0129] Seepage height: 7.2 mm;

[0130] Carbonization depth: 5.2 mm;

[0131] Initial crack width: 0.45 mm; crack width after 28 days of self-healing: 0.13 mm; healing rate: 72%.

[0132] Example 5

[0133] (1) Raw material usage

[0134] Except that the mass fraction of sodium alginate aqueous solution was changed to 2.5%, the other parameters were the same as in Example 1.

[0135] (2) Preparation method

[0136] Same as Example 1.

[0137] (3) Performance results

[0138] 28-day compressive strength: 60 MPa;

[0139] 28-day flexural strength: 9.0 MPa;

[0140] Chloride ion diffusion coefficient: 4.1 × 10⁻⁶ -12 m 2 / s;

[0141] Seepage height: 6.8 mm;

[0142] Carbonization depth: 5 mm;

[0143] Initial crack width: 0.4 mm; crack width after 28 days of self-healing: 0.1 mm; healing rate: 75%.

[0144] Example 6

[0145] (1) Raw material usage

[0146] Except that the mass fraction of the chitosan acidic solution was changed to 0.2%, the other parameters were the same as in Example 1.

[0147] (2) Preparation method

[0148] Same as Example 1.

[0149] (3) Performance results

[0150] 28-day compressive strength: 58 MPa;

[0151] 28-day flexural strength: 8.2 MPa;

[0152] Chloride ion diffusion coefficient: 4.6 × 10⁻⁶ -12 m 2 / s;

[0153] Seepage height: 7.2 mm;

[0154] Carbonization depth: 5.3 mm;

[0155] Initial crack width: 0.29 mm; crack width after 28 days of self-healing: 0.05 mm; healing rate: 71%.

[0156] Example 7

[0157] (1) Raw material usage

[0158] Except that the mass fraction of the chitosan acidic solution was changed to 0.6%, the other parameters were the same as in Example 1.

[0159] (2) Preparation method

[0160] Same as Example 1.

[0161] (3) Performance results

[0162] 28-day compressive strength: 59 MPa;

[0163] 28-day flexural strength: 8.7 MPa;

[0164] Chloride ion diffusion coefficient: 4.6 × 10⁻⁶ -12 m 2 / s;

[0165] Seepage height: 7 mm;

[0166] Carbonization depth: 5.6 mm;

[0167] Initial crack width: 0.47 mm; crack width after 28 days of self-healing: 0.14 mm; healing rate: 70%.

[0168] Comparative Example 1: Homogeneous fully recycled aggregate geopolymer reinforced concrete pipe

[0169] (1) Raw material usage (kg / m³) 3 )

[0170] Inner layer: 900g recycled coarse aggregate; 800g recycled fine aggregate; 480g geopolymer cementitious material (240g fly ash, 144g slag, 96g steel slag); 230g alkali activator solution; 25g mixing water; 0g fiber; 0g microcapsules;

[0171] Outer layer: 900g recycled coarse aggregate; 800g recycled fine aggregate; 480g geopolymer cementitious material (240g fly ash, 144g slag, 96g steel slag); 230g alkali activator solution; 25g mixing water; 0g fiber; 0g microcapsules.

[0172] (2) Preparation method

[0173] a) Preparation of geopolymer mortar: First, dry mix the recycled fine aggregate, fly ash, slag and steel slag for 60 s, then add alkali activator solution and mixing water and continue wet mixing for 120 s, controlling the flowability of the mortar to 180-200 mm.

[0174] b) Preparation of geopolymer concrete: First, dry mix recycled coarse aggregate, recycled fine aggregate, fly ash, slag, steel slag, fiber and microcapsules for 60 s, then add alkali activator solution and mixing water and continue wet mixing for 120 s, controlling the flowability of the concrete at the outlet to 180-200 mm.

[0175] c) Fabricate the steel reinforcement cage and place it into the pipe mold;

[0176] d) Using centrifugal pipe-making technology, the polymer concrete is first added to the barrel and then pumped to the centrifugal pipe-making machine. The pipe is then cast using centrifugal technology until the specified pipe wall thickness is achieved, thus realizing one-time composite molding.

[0177] e) After centrifugal molding, the concrete pipe is steam cured at 60℃ for 8 hours, and then wet cured at room temperature for 28 days to obtain the finished concrete pipe.

[0178] (3) Performance results

[0179] 28-day compressive strength: 55 MPa;

[0180] 28-day flexural strength: 7.5 MPa;

[0181] Chloride ion diffusion coefficient: 7.2 × 10⁻¹² m² / s;

[0182] Seepage height: 20 mm;

[0183] Crack healing rate at 28 days: 8%.

[0184] Comparative Example 2: Reinforced Concrete Pipe with All-Recycled Aggregate Geopolymer Without Microcapsules

[0185] (1) Raw material usage (kg / m³) 3 )

[0186] Inner layer: 1356 recycled fine aggregate (=1350+6); 600 geopolymer cementitious material (300 fly ash, 180 slag, 120 steel slag); 270 alkali activator solution; 35 mixing water; 0 microcapsules;

[0187] Outer layer: 880 recycled coarse aggregate; 784.8 recycled fine aggregate (=780+4.8); 480 geopolymer cementitious material (240 fly ash, 144 slag, 96 steel slag); 230 alkali activator solution; 25 mixing water; 14.7 fiber; 0 microcapsules.

[0188] (2) Preparation method

[0189] The preparation method is the same as that of Comparative Example 1.

[0190] (3) Performance results

[0191] 28-day outer layer compressive strength: 60 MPa;

[0192] 28-day inner layer compressive strength: 54 MPa;

[0193] Chloride ion diffusion coefficient: 6.3 × 10⁻⁶ -12 m 2 / s;

[0194] Seepage height: 13.5 mm;

[0195] Crack size after 28 days: 0.22 mm (healing rate 27%).

Claims

1. A full-recycled aggregate geopolymer ductile reinforced concrete pipe based on functional gradient design and microcapsule self-healing for municipal sewerage pipelines, characterized by: Along the radial direction, it includes at least an inner layer and an outer layer that are sequentially arranged and composited, forming an integral structure; The inner layer is a dense, impermeable layer, cast from a geopolymer mortar without coarse aggregate, and a steel reinforcement skeleton is provided within the inner layer; the geopolymer mortar includes recycled fine aggregate, geopolymer cementitious material, and microcapsules; the microcapsules are uniformly distributed in the geopolymer mortar; The outer layer is a reinforced load-bearing and crack-resistant layer, which is cast from geopolymer concrete and has a steel reinforcement skeleton inside; the geopolymer concrete includes recycled coarse aggregate, recycled fine aggregate, geopolymer cementitious material, fiber and microcapsules; the fiber and microcapsules are uniformly distributed in the geopolymer concrete; The geopolymer concrete and geopolymer mortar are compositely formed in the same pipe mold using a centrifugal pipe-making process. The inner and outer layers exhibit a gradient change in the radial direction in one of the following parameters: content of cementitious materials, aggregate particle size composition or fiber content, and the content of geopolymer cementitious materials in the inner layer is higher than that in the outer layer. The geopolymer cementitious material is obtained by alkaline activation reaction using fly ash, slag and steel slag as precursors; the mass ratio of fly ash, slag and steel slag is 5:3:

2. The microcapsules contain bacterial liquid and nutrients with calcium carbonate mineralization ability, enabling the concrete pipe to autonomously repair microcracks during service by inducing calcium carbonate precipitation through microorganisms. The preparation method of the microcapsules includes: mixing a sodium alginate aqueous solution with a mass fraction of 1.5%-2.5% with bacterial culture with calcium carbonate mineralization ability cultured to the logarithmic phase and its nutrient components, dropping the mixture into a CaCl2 cross-linking curing bath to gel into spheres, then immersing the spheres in an acidic chitosan solution with a mass fraction of 0.2-0.6% for secondary chitosan coating, followed by low-temperature drying and sealing for storage, and then immersing the coated microcapsules in a diluted silica sol / water glass solution to form a thin inorganic outer layer to enhance alkali resistance. The resulting microcapsules have a median particle size D50 of 300 μm and an average wall thickness of 15 μm. The microcapsules are incorporated into the polymer mortar at a dosage of 1%-5% of the mass of the polymer cementitious material in the mortar; the microcapsules are incorporated into the polymer concrete at a dosage of 1%-5% of the mass of the polymer cementitious material in the polymer concrete. The steel reinforcement cage includes circumferential steel bars and longitudinal steel bars, which are connected to form a steel cage structure and arranged along the perimeter of the pipe.

2. The concrete pipe according to claim 1, characterized in that The alkaline activation reaction uses sodium hydroxide, water glass, or a combination of both as the alkaline activator.

3. The concrete pipe of claim 1, wherein The fiber is steel fiber, polypropylene fiber, basalt fiber or any combination thereof, and the volume fraction of the fiber is 0.5%-1.5% of the volume of the geopolymer cementitious material in the geopolymer concrete.

4. The concrete pipe according to claim 1, characterized in that, The diameter of the circumferential reinforcing bars is ≥4.0 mm, and the net spacing of the circumferential reinforcing bars is 35-120 mm; the diameter of the longitudinal reinforcing bars is ≥4.0 mm, the spacing of the longitudinal reinforcing bars is ≤400 mm, and the number of longitudinal reinforcing bars is ≥6. When the pipe wall thickness is ≤100 mm, single-layer reinforcement is used, and the steel reinforcement cage is set at 2 / 5 of the distance from the inner wall of the pipe; when the pipe wall thickness is >100 mm, double-layer reinforcement is used, and the inner and outer concrete cover thickness of the circumferential reinforcement is not less than 20 mm, and the inner concrete cover thickness of the longitudinal reinforcement is not less than 15 mm.

5. The concrete pipe according to claim 1, characterized in that, The recycled coarse aggregate and recycled fine aggregate are both derived from construction solid waste and are obtained through crushing, screening, impurity removal and gradation adjustment.

6. The method for preparing a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Step A0, preparation of microcapsules: A 1.5%-2.5% sodium alginate aqueous solution was mixed with bacterial culture with calcium carbonate mineralization ability cultured to the logarithmic phase and its nutrient components. The mixture was then dropped into a CaCl2 cross-linking curing bath to gel into spheres. After being immersed in a 0.2-0.6% chitosan acidic solution for secondary chitosan coating, the microcapsules were dried at low temperature and sealed for storage. The coated microcapsules were then immersed in a diluted silica sol / water glass solution to form a thin inorganic outer layer to enhance alkali resistance, resulting in microcapsules with a median particle size D50 of 300 μm and an average wall thickness of 15 μm. Step A1, preparing geopolymer mortar: dry mix the recycled fine aggregate, geopolymer cementitious material and microcapsules evenly, then add the alkali activator solution and mixing water and continue to wet mix evenly; Step A2, preparing geopolymer concrete: Dry mix recycled coarse aggregate, recycled fine aggregate, geopolymer cementitious material, fiber and microcapsule evenly, then add alkali activator solution and mixing water and continue to wet mix evenly; The alkaline activator solution is a mixture of sodium hydroxide solution and water glass, wherein the concentration of the sodium hydroxide solution is 8-12M and the modulus of the water glass is M=2.0-2.5; the liquid-to-solid ratio of the alkaline activator solution in step A1 to the geopolymer cementitious material in step A1 is 0.40-0.48; the liquid-to-solid ratio of the alkaline activator solution in step A2 to the geopolymer cementitious material in step A2 is 0.40-0.

48. Step A3: Fabricate the steel reinforcement cage and place it into the pipe mold, using positioning measures to ensure the steel reinforcement cage is in the designed position in the thickness direction of the pipe body; Step A4: Using centrifugal pipe-making technology, polymer concrete and polymer mortar are compositely molded in the same pipe mold: First, polymer concrete is added to cylinder A, and polymer mortar is added to cylinder B. The polymer concrete in cylinder A is pumped to the centrifugal pipe-making machine. The outer layer of the pipe is cast using centrifugal technology. After the required thickness of the outer layer is reached, the same method is used to simultaneously pump polymer concrete and polymer mortar into the pipe-making machine for 1 minute. Then, the pumping of polymer concrete is stopped, and only the pumping of polymer mortar is continued. The inner layer of the pipe is cast using centrifugal technology until the specified thickness of the inner layer is reached, thus achieving one-time composite molding and obtaining a pipe with inner and outer layers. Step A5: After centrifugation molding, the concrete pipe is cured to obtain a fully recycled aggregate geopolymer tough reinforced concrete pipe based on functional gradient design and microcapsule self-healing.

Citation Information

Patent Citations

  • Green low-carbon concrete prepared based on recycled aggregate and preparation method of green low-carbon concrete

    CN120647271A

  • Prestressed steel cylinder concrete jacking pipe with novel structure

    CN213018148U